Fighting for air the battle to control America's media - Klinenberg, Eric 1970- (Metropolitan Books, 2007)
An investigative work on the corporate takeover of local news and what it means for all Americans. Sociologist Klinenberg takes us into the world of preprogrammed radio shows, empty television news studios, and copycat newspapers to show how corporate ownership and control of local media has remade American political and cultural life. Klinenberg argues that the demise of truly local media stems from the federal government's malign neglect, as the agencies charged with ensuring diversity and open competition have ceded control to the very conglomerates that consistently undermine these values and goals. "Big media" may not be here to stay, however. This book reveals a rising generation of new media activists and citizen journalists--a coalition of liberals and conservatives--who are demanding and even creating the local coverage they need and deserve.--From publisher description.
Includes bibliographical references (p. [297]-322) and index
Keywords: Médias - Influence; Broadcasting policy -- United States; Mass media policy -- United States; Massenmedien; USA